2013
DOI: 10.3168/jds.2012-5950
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bifidobacterium bifidum BF-1 on gastric protection and mucin production in an acute gastric injury rat model

Abstract: Homeostasis in the stomach environment is maintained by the balance of protective factors such as gastric mucus and aggressive factors such as gastric acid, stress, alcohol, and drugs. An overload of aggressive factors that upsets this balance can induce gastric injury. Fermented milk that contains Bifidobacterium bifidum BF-1 (BF-1), a probiotic strain, and Streptococcus thermophilus YIT 2021 (ST) is known to improve Helicobacter pylori-associated gastritis in humans. Here, we investigated the gastroprotectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 12 publications
3
33
0
2
Order By: Relevance
“…It has also been demonstrated that B. bifidum YIT 10347 has potential to inhibit H. pylori activity and the induction of IL-8 in H. pylori-infected gastric epithelial cells via the regulation of nuclear factor κB (NF-κB) signaling pathways (Shirasawa et al, 2010), to alleviate drug-induced acute injury due to the stimulated production of gastroprotective mucin in rat stomach (Gomi et al, 2013), and to adhere highly to both human gastric epithelial cells (GCIY cells) and mucin Figure 3. The ingestion of fermented milk containing Bifidobacterium bifidum YIT 10347 reduced the prevalence of lower abdominal symptoms in adults.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that B. bifidum YIT 10347 has potential to inhibit H. pylori activity and the induction of IL-8 in H. pylori-infected gastric epithelial cells via the regulation of nuclear factor κB (NF-κB) signaling pathways (Shirasawa et al, 2010), to alleviate drug-induced acute injury due to the stimulated production of gastroprotective mucin in rat stomach (Gomi et al, 2013), and to adhere highly to both human gastric epithelial cells (GCIY cells) and mucin Figure 3. The ingestion of fermented milk containing Bifidobacterium bifidum YIT 10347 reduced the prevalence of lower abdominal symptoms in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Living B. bifidum BF-1 and S. thermophilus YIT 2021 or vehicle was orally administered to rats, and acid-ethanol gastric injury was induced 2 h later. Mucin 5ac (muc5ac) gene expression in gastric corpus samples and gastric mucin production in stomach samples from the B. bifidum BF-1 group, but not the S. thermophilus YIT 2021 group, were significantly higher than those in the respective samples from the vehicle group [86] . Mirpuri et al [87] (2012) evaluated the enteral administration of LGG in mice with intestinal injury due to the administration of platelet-activating factor (PAF) and LPS.…”
Section: Other Inflammatory Disordersmentioning
confidence: 98%
“…Extensive research has been performed on the efficacy of various Lactobacillus strains on gastric ulcers (Dharmani et al, 2013;Khoder et al, 2016) either as single therapeutic agents or in combination with antibiotics (Boltin, 2016;Goderska et al, 2018). The majority of the investigated strains have been shown to inhibit or protect the gastric mucosal barrier through the up-regulation of prostaglandin E2 (Uchida and Kurakazu, 2004;Gotteland et al, 2006;Lam et al, 2007;Uchida et al, 2010), enhancement of mucus secretion (Gomi et al, 2013) or the regulation of inflammatory responses (Konturek et al, 2009;Şenol et al, 2014). Moreover, not only do these probiotics have prophylactic effects, but some of them also exert therapeutic effects through the enhancement of epithelial growth (Singh and Kaur, 2012), promotion of angiogenesis (Dharmani et al, 2013) and up-regulation effect on anti-inflammatory cytokines expression (Virchenko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%